Regulation of chloroplast gene expression: light activated translation - Mayfield, Stephen (Henry Stewart Talks, 2007)
Chloroplast gene expression is primarily regulated during translation, Light activates translation via a redox cascade initiated by photosynthetic electron transport, Plastid specific translation factors and RNA elements interact with chloroplast ribosomes to facilitate translation initiation